Development of moral education in the UAE: lessons to be learned. (4th May 2019) - Pring, Richard
ABSTRACT: The United Arab Emirates (UAE) is making it a requirement of all schools within the Emirates (both public and private) to follow a programme of moral education (MEP), at all ages from grades 1 to 13, which is designed centrally. Explicitly secular and humanist in its approach, this is a remarkable development in a country where Islam is the official religion and where traditional practices and values are deeply rooted. However, it provides an example of an education initiative designed to contribute to a national strategic ambition—that of developing the UAE as a progressive, enlightened country, and one where its residents share a common culture despite the diversity of their origins. This paper describes the programme and sets it in the context of 'virtue education', following a philosophical and ethical tradition to which both Arab and Western philosophers have contributed.